2021
DOI: 10.26444/aaem/126020
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroergotamine affects spatial behavior and neurotransmission in the central nervous system of Wistar rats

Abstract: affects spatial behavior and neurotransmission in the central nervous system of Wistar rats. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Another explanation of the lack of effect of famotidine on reversing the beneficial effects of DHE on spatial memory in the present study is associated with changes in other neurotransmitter systems produced by DHE, which can contribute to their effect on memory. Piechal A. et al, 2021 demonstrated that administration of DHE to adult male Wistar Albino Glaxo rats produced changes in the concentration of monoaminergic neurotransmitters and their metabolites in the prefrontal cortex, striatum, cerebellum, medulla oblongata, and spinal cord [35]. Due to the above commentaries, it is necessary to continue with the exploration of DHE's effects on memory in additional behavioral assays.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation of the lack of effect of famotidine on reversing the beneficial effects of DHE on spatial memory in the present study is associated with changes in other neurotransmitter systems produced by DHE, which can contribute to their effect on memory. Piechal A. et al, 2021 demonstrated that administration of DHE to adult male Wistar Albino Glaxo rats produced changes in the concentration of monoaminergic neurotransmitters and their metabolites in the prefrontal cortex, striatum, cerebellum, medulla oblongata, and spinal cord [35]. Due to the above commentaries, it is necessary to continue with the exploration of DHE's effects on memory in additional behavioral assays.…”
Section: Discussionmentioning
confidence: 99%
“…Although oral administration of dihydroergotamine to adult male Wistar Albino Glaxo did not influence the learning processes, dihydroergotamine treatment produced changes in the concentration of monoaminergic neurotransmitters and their metabolites in the prefrontal cortex, striatum, cerebellum, medulla oblongata and spinal cord [ 35 ]. In a similar way, although vilazodone has not shown improvements in visuospatial memory in healthy middle-aged female mice, its effects on animal models of cognitive impairment have not been explored [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structure of DHE is similar to that of many natural neurotransmitters, including epinephrine, norepinephrine, dopamine, and serotonin[ 26 ]. It can modulate noradrenergic, serotonergic, and dopaminergic neurotransmission[ 34 ]. DHE is an adrenergic receptor antagonist used to treat severe orthostatic hypotension, migraine, and headache[ 26 ], which can bind with various receptors.…”
Section: Discussionmentioning
confidence: 99%